A study of cesarean section rate by using modified Robson's ten group classification system - Patel, Meha K.; Prajapati, Saloni M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: High caesarean section rate worldwide including India is matter of concern. The Robson’s Ten-group classification system allows critical analysis of caesarean deliveries according to characteristics of pregnancy. The objective was to analyze caesarean section rates in a tertiary care centre according to Modified Robson’s ten groups classification. Methods: This retrospective study was conducted at GMERS Gotri Medical College, Vadodara, Gujarat, India. All patients who delivered between August 2018 and March 2019, were included in the study. Women were classified in 10 groups according to modified Robson’s classification using their maternal characteristics and obstetric history. For each group, authors calculated the caesarean section rate within the group and its absolute and relative contribution to the overall caesarean rate. Results: Total number of delivery in my study institute in 8 months was 1531 out of them 456 was cesarean section, so the overall caesarean section rate was 29.78%. The main contributions to overall caesarean rate was 40.78% by group 5 (previous CS, singleton, cephalic, >37weeks) followed by 14.25% by group 1 (nullipara, singleton, cephalic, >37 weeks, spontaneous labour), 11.40% by group 2 (nullipara, singleton, cephalic,>37 weeks, induced or CS before labour). CS rates among various group ranges from 100% among women with abnormal lie (group 9) to 98.4% in previous CS (group 5), 84% in nulliparous breech (group 6), 58% in multiparous breech (group 7) and least 8.2% in multipara spontaneous labour (group 3). Conclusions: The Robson’s classification is easy to use. It is time to implement obstetric audit to lower the overall CS rates.